Fiscal federalism and tax enforcement - Timm Bönke; Beate Joachimsen; Carsten Schröder (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
In many countries organized as federations, fiscal-equalization schemes have been implemented to mitigate vertical or horizontal imbalances. Such schemes usually imply that the member states of the federation can only partly internalize marginal tax revenue before redistribution. Aside from this internalized revenue, referred to as the marginal tax-back rate, the remainder is redistributed. We investigate the extent to which extent state-level authorities in such federation under-exploit their tax bases. By means of a stylized model we show that the member states have an incentive to align the effective tax rates on their residents with the level of the tax-back rate. We empirically test the model using state-level and micro-level taxpayer data, OLS regressions and natural experiments. Our empirical findings support the results from our theoretical model. Particularly, we find that states with a higher marginal tax-back rate exploit the tax base to a higher extent.
Keywords: C21; H21; H77; 330; fiscal federalism; fiscal externalities; natural experiment; treatment analysis; statistical matching